Preparation of biomass-based hydrogels and their efficient heavy metal removal from aqueous solution - Zhang, Mingyue; Zhou, Yaru; Wang, Fangling; Chen, Zeshao; Zhao, Xu; Duan, Weidong; Yin, Guangting; Yang, Xinling; Li, Junfeng; Yin, Quanyu; Zhao, Mingqin (Frontiers in Chemistry, 2022)
In this work, a porous tobacco straw-based polyacrylic acid hydrogel STS-PAA with high adsorption performance was prepared by polymerizing pretreated waste tobacco straw (TS) with acrylic acid/potassium acrylate by UV radiation initiation. The adsorption performance of metal ions was investigated. The effects of different temperatures (25°C, 35°C, and 45°C), adsorption times (1–420 min), pH values (2.0–6.0) and initial concentrations (0.25–4.0 mmol L−1) of metal ions on the adsorption amount of heavy metal ions were investigated. The results showed that the hydrogel had a high removal rate of Pb2+, Cd2+ and Hg2+ in aqueous solution. The adsorption of Pb2+ was particularly effective. When C0 = 4.0 mmol L−1, pH = 6, the equilibrium adsorption amount of Pb2+, Cd2+ and Hg2+ reached 1.49 mmol g−1, 1.02 mmol L−1 and 0.94 mmol g−1, respectively. The chemical structure and morphology of the hydrogels were characterized by FT-IR, EDS, SEM and XPS. The Langmuir model fits well with the adsorption system. The kinetic data suggest the adsorption of Pb2+, Cd2+ and Hg2+ follow the pseudo-first-order model. This indicates that STS-PAA adsorption of three heavy metal ions is monolayer physical adsorption. Thermodynamic analysis shows that the adsorption of Pb2+, Cd2+ and Hg2+ by STS-PAA is an endothermic (ΔH>0) entropy increase (ΔS>0) non-spontaneous reaction.